Odpowiedź :
(x+3)²-(x-5)²=16(x-1)
x²+6x+9-x²+10x-25=16x-16
6x+9+10x-25=16x-16
6x+10x-16x=16+25-9
0=0
x²+6x+9-x²+10x-25=16x-16
6x+9+10x-25=16x-16
6x+10x-16x=16+25-9
0=0
(x+3)²-(x-5)²=16(x-1)
(x+3)*(x+3)-(x-5)*(x-5)=16x-16
(x²+3x+3x+9)-(x²-5x-5x+25)=16x-16
x²+3x+3x+9-x²+5x+5x-25=16x-16
16x-16=16x-16
0=0
(x+3)*(x+3)-(x-5)*(x-5)=16x-16
(x²+3x+3x+9)-(x²-5x-5x+25)=16x-16
x²+3x+3x+9-x²+5x+5x-25=16x-16
16x-16=16x-16
0=0
x²+6x+9-x²+10x-25=16x-16
16x+9-25=16x-16
-16=-16
Równanie sprzeczne – nie ma rozwiązania.
16x+9-25=16x-16
-16=-16
Równanie sprzeczne – nie ma rozwiązania.